(untitled) (European Journal of Pure and Applied Mathematics, 2026)
Shahzad et al. [RACSAM 111 (2017) 307-324] introduced the notion of (A,S)- contractions which unifies several well known nonlinear type contractions (e.g. R-contractions, Z-contractions, L-contractions etc.) in one go.In this paper we extend the notion of (A,S)-contractions from Shahzad et al. S to non-self mappings in a metric space with a w-distance. Then we prove some new proximity point theorems for the aforementioned type of mappings. This paper is a continuation of our previous papers Ko2,Ko1.